The Integration between Process Reengineering and Cost-Accounting System Based on Activity & its Contribution to Improve Organisation Performance: Case of Small Industries - Hicheme , MEZHOUD; Meryem , KALLECHE (Milev Journal of Research and Studies, 2020)
This study aims at investigating the contribution of the achievement between Business Process Reengineering method and Activity Based Costing System in ameliorating enterprises through raising its performance. Accordingly, a sample of Small and Medium-sized enterprises located in the industrial area of Setif was studied, through the collection of data from a sample of 32 enterprises, as 76 questionnaires were recovered and the data collected was used in the statistical analysis of the variables. The importance of Business Process Reengineering method was clearly demonstrated in this research in regards to Small and Medium-sized enterprises. Through the contribution of making it closer to the costumer who is more aware of his needs and desires. In addition to that, the results of the research show that the integration between Business Process Reengineering, and Activity Based Costing System ABC contributes in understanding precisely the reasons of costs, behaviour, and the practiced production activities which add value through production steps expressed by operations, which in turn contribute in ameliorating the performance of the enterprise.